Red state Christians : understanding the voters who elected Donald Trump - Denker, Angela (Fortress Press, 2019)
Donald Trump won more Evangelical Christian votes than any candidate in history on his way to winning the 2016 US presidential election. Veteran journalist Angela Denker set out to uncover why, traveling the United States for a year, meeting the people who support Trump, and listening to their rationale. A must-read for those hoping to truly understand how Donald Trump became president.